Ultra‐small PtNi bimetallic encapsulated in silicalite‐1 zeolite with fine‐tuned surface acidity for selective conversion of levulinic acid. (7th November 2022) - Wang, Yanyun; Bao, Jiehua; Zuo, Changjiang; Dong, Guomeng; Sheng, Xiaoli; Huang, Yuzhong; Zhang, Yiwei; Zhou, Yuming
Abstract : Exploration of levulinic acid (LA) hydrogenation to γ‐valerolactone (GVL) contributes to the conversion from carbohydrates to valuable fuels and chemicals. Here, we obtained a series of ultra‐small PtNix bimetallic composite catalysts encapsulated in silicalite‐1 zeolite (S‐1) via a one‐pot synthesis strategy protected by tetra(p‐carboxyphenyl)porphyrin (TCPP) ligands. The catalytic results showed that PtNi3 @S‐1 (TCPP) exhibited the most active catalytic performance (95.7% LA conversion and 93.8% GVL selectivity) under optimized conditions. The characterization results indicate that ligand modification and bimetallic synergy play an important role in enhancing the catalytic activity. The introduction of TCPP provides a guarantee for the homogeneous encapsulation of PtNi3 in S‐1 zeolite at sub‐nanometer size. The electronic interaction of PtNi bimetallic, high dispersibility of active components, improved surface acidity and excellent stability co‐contribute to the satisfactory hydrogenation activity. Abstract : Silicalite‐1 encapsulated ultra‐small PtNix bimetallic catalyst were prepared. Porphyrin ligands act as protective agents to aid in metal dispersion. Sub‐nanometer PtNix bimetals are uniformly encapsulated in the zeolite channels. Metal‐zeolite interfacial interactions are enhanced due to the addition of ligand. The synergistic effect of the alloy enhances the catalytic activity.